Use of Aesculus hippocastanum L. as a biomonitor of heavy metal pollution - (:unkn) unknown (PAKISTAN BOTANICAL SOC, 2006)
Aesculus hippocastanum was studied as a possible biomonitor of the heavy metal pollution in the region of Thrace situated in the European part of Turkey. The urban roadside, city centre, and suburban sites were investigated. The Pb, Cd, Zn and Cu concentrations varied between 0.0200.051; 0.001-0.002 0.391-0.594; 0.256-0.38-7 g g(-1) dry weight in the washed leaves, between 0.023-0.119 0.002-0.068; 0.374-0.532 0.322-0.466 mu g g(-1) dry weight in the unwashed leaves, between 0.063-0.628; 0.005- 0.006-, 0.406-0.660; 0.345-1.026 Ag g(-1) dry weight in the bark respectively. In the soils supporting these plants the values of Pb, Cd, Zn and Cu varied between 0.812-6.745; 0.002-0.006; 2.196-4.598; 0.517-1.117 mu gg(-1) dry weight respectively. When we compare the concentrations of the heavy metals in the leaves, bark and soils, we can see that the values in the urban roadside are higher than other sites. According to these results concentration of C C:1 heavy metals in A. hippocastanum did not exceed the upper limit. A highly linear regression was obtained for Pb, Zn and Cu between concentrations of the element in surface soil and in the washed leaves of plant but the correlation in the case of Cd was insignificant.
Keywords: Aesculus hippocostanum; heavy metals; biomonitor; thrace; Turkey